Child portraits. Representations of the child body in children’s illustration and literature: some interpretative categories. - Terrusi, Marcella (Rivista di Storia dell’Educazione, 2017)
A critical path in the history of children’s illustration and literature, discovering the portraits and metaphors of childhood that attract the scholar’s attention to pedagogical thought on the imagination, and some ideas for interpreting representations of the child body.